If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10 = -7x + 7 Reorder the terms: 10 + 5x = -7x + 7 Reorder the terms: 10 + 5x = 7 + -7x Solving 10 + 5x = 7 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 10 + 5x + 7x = 7 + -7x + 7x Combine like terms: 5x + 7x = 12x 10 + 12x = 7 + -7x + 7x Combine like terms: -7x + 7x = 0 10 + 12x = 7 + 0 10 + 12x = 7 Add '-10' to each side of the equation. 10 + -10 + 12x = 7 + -10 Combine like terms: 10 + -10 = 0 0 + 12x = 7 + -10 12x = 7 + -10 Combine like terms: 7 + -10 = -3 12x = -3 Divide each side by '12'. x = -0.25 Simplifying x = -0.25
| 1=7-2x+8x | | 6x+80=60-10x | | 2/3(x-4)-3(x-5)=3x-7 | | 5x-15+2x=7+7x-22 | | 60=-6(1-b)+5(5b+7) | | 6.5/0.0011= | | 3(4+x)=26 | | 8t/6=3*4 | | (4)(-9)(2)= | | 7a-(3a-8)=12 | | 4/5n-1/5-=/n | | -x/5=.2 | | -4-1/2y=7/4 | | 4x-6=-5x+21 | | 8x-10=-12x+60 | | -1=b | | 3250-m=1500+2m-1000 | | 4n^2=48 | | 3m^2=75m | | 7d-12+2d+5=18 | | 3x-9y=51 | | ax-3b=4c | | -2/5--1/5 | | -7x+16=65 | | D(d-5)=0 | | f(x)=2x^2-2x-4 | | -4(4-d-5)= | | 3k/7=6 | | 6p+6(-5p-8)=-168 | | 555+33y=3(230-2y) | | 27X+10=29x | | 3d-20=d |